Danish and German silent cinema : towards a common film culture - Sørensen, Lars-Martin; Sørensen, Lars-Martin; Tybjerg, Casper; Tybjerg, Casper (Edinburgh University Press, 2023)
"The book examines how Danish and German film interacted with one another from 1910 through World War I till the advent of sound around 1930. The film businesses of the two countries were closely connected, and many film professionals crossed back and forth across national borders.The studies in this book include production and distribution history, censorship, celebrity studies, and aesthetic analysis. They contribute to European film and cultural history through extensive empirical investigation of films, persons and companies. The underlying perspective is that of entangled film history, an approach that stresses cross-border interchanges and mutual influences. Written by an international team of scholars, the book marks the conclusion of a four-year collective research project running alongside the stumfilm.dk initiative to digitise the entire Danish silent film heritage"--